Pupil‐sparing cranial nerve III palsy after intranasal cocaine treatment for cluster headache - Philip M. Davis; Mark L. Riddle (Journal of the American College of Emergency Physicians Open)
Abstract This case report discusses a cranial nerve III palsy in a 47‐year‐old, type II diabetic man that originally presented with a cluster headache that was treated with 100% oxygen by nasal cannula, 975 mg Tylenol, and 100 mg of Imitrex without any symptom relief. He then received a sphenopalatine fossa block using 1 ampule of 4% cocaine. Three days after medicinal, intranasal cocaine for treatment of a cluster headache, the patient presented with a cranial nerve III palsy with spontaneous resolution in 4 months without any intervention. Previously, intranasal cocaine had been standard treatment for cluster headaches; however, recently lidocaine has come into favor for the sphenopalatine block. Intranasal cocaine has been associated with cerebrovascular accidents, even in young adults. The time from cocaine use to cerebrovascular accident can range from hours to years. This known side effect of intranasal cocaine in young, otherwise healthy individuals should be considered when this medication is being used to treat headache, especially in higher risk patients. Therefore, when considering a sphenopalatine nerve block for treatment of headaches, both cluster and migraine, lidocaine should be the preferential treatment over intra‐nasal cocaine.